The brazilian students' performance and the PISA assessment: some aspects for discussion - Andreia Freitas Zompero; Helenara Regina Sampaio Figueiredo; Karen Mayara Vieira (Universidad Distrital Francisco José de Caldas, 2016)
This study was carried out with students from the ninth grade called as "A" that does not develop science learning activities and another one called school "B" that does. This study instrument was two questions from the PISA, the question A of the activity named "The Diary of Semmelweis" and the activity question "Flies". We have analyzed the students the answers as "Total", "Partial" and "Zero". We have found out that the percentages of "Total and Partial" responses in activity 1 were higher in School "B" when compared to School "A"; whereas in activity 2, both schools had no "Total" answers performed. These results indicate that the skills and competencies related to scientific research must be developed in both schools.